Desenvolvimento de atividades de pesquisa nos Institutos Federais de Educação, Ciência e Tecnologia do Estado de Minas Gerais - Jose Eduardo Borges Moreira (2017)
The main objective of this work is to carry out a research on the development of research activities in the Federal Education, Science and Technology Institutes - Federal Institutes (IF), of Minas Gerais state, from 2008 to 2014. The investigation of factors that can influence the offering and implementation of research activities in these Federal Institutes occurred through the analysis of specific legislation and documents on education produced in the country, especially from the 1990s. Furthermore, additional data about the development of research in these Federal Institutes were collected through the application of electronic questionnaires and interviews with teachers and managers. Theoretical studies were made in order to show evidences that the historical duality of education in the country, between general education and training for work, is maintained even with the completion of the educational reforms of vocational education promoted by the government of President Lula, starting in 2003. Taking as its starting point the first term in office of Partido dos Trabalhadores (PT) at the federal level by the President Lula's government in 2003, this work is constructed from two axes: 1) the discussion about the schooling duality in the country, between general education and training for work, and 2) the development of research activities in the Federal Institutes from 2008 to 2014. Created in 2008, the Federal Institutes represent numerically the largest expansion of the Federal Network of Vocational Education of all time in the country. Because of that, in 2012 the Federal General Accounting Office (TCU) conducted an audit that resulted in the publication of a report with a series of recommendations to improve the performance of these Federal Institutes. Some of the questions pointed out by the TCU served as the starting point for the development of this research, which supports the hypothesis that vocational education in Brazil has been linked to a series of public policies that have contributed to maintaining a lower formal qualification of teachers from Federal Institutes in relation to the teaching career of the Federal Universities which could disadvantage the development of research activities at these Federal Institutes.